2003
DOI: 10.1067/mcp.2003.23
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the suitability of intravenous midazolam as an in vivo marker for hepatic cytochrome P4503A activity

Abstract: Phenotyping is used to characterize hepatic drugmetabolizing enzyme activity as influenced by pharmacogenetics and environmental exposure. In many instances, phenotyping for hepatic drug-metabolizing enzyme activity involves the intravenous administration of a suitable biomarker (often a drug) and the determination of its total systemic clearance (CL). This procedure assumes that CL is correlated with the intrinsic hepatic clearance of the drug from plasma (CL int ), a measure of intrinsic hepatic enzyme activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 9 publications
2
59
0
Order By: Relevance
“…6 − 8 The pharmacokinetic properties of midazolam, however, include significant variability in metabolic clearance and numerous drug−drug interactions. 9,10 Dosedependent respiratory depression, prolonged sedation and cognitive disturbances may occur, particularly in elderly patients and in those with hepatic or renal dysfunction. 11,12 Dexmedetomidine is an α 2 -adrenoreceptor agonist with a unique mechanism of action: it induces sedation via receptors within the locus coeruleus, analgesia via receptors in the spinal cord and attenuation of the stress response without significant respiratory depression.…”
Section: mentioning
confidence: 99%
“…6 − 8 The pharmacokinetic properties of midazolam, however, include significant variability in metabolic clearance and numerous drug−drug interactions. 9,10 Dosedependent respiratory depression, prolonged sedation and cognitive disturbances may occur, particularly in elderly patients and in those with hepatic or renal dysfunction. 11,12 Dexmedetomidine is an α 2 -adrenoreceptor agonist with a unique mechanism of action: it induces sedation via receptors within the locus coeruleus, analgesia via receptors in the spinal cord and attenuation of the stress response without significant respiratory depression.…”
Section: mentioning
confidence: 99%
“…Various noninvasive in vivo probes for evaluating CYP3A activity have been described and several have been shown to correlate with drug clearance (3). The most widely tested and accepted CYP3A probes are midazolam and erythromycin, although selection of the ideal CYP3A-phenotyping probe remains controversial (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…injection over ϳ1 minute. Breath samples were collected in balloons postinjection at 5,10,15,20,25,30, and 40 minutes. Samples were shipped to Metabolic Solutions for measurement of breath carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…This is unfortunate, because CYP3A4 is the most abundant hepatic and intestinal cytochrome P450, catalyzes the metabolism of more than half of all drugs, and represents the primary route of elimination for many drugs. Some studies have reported a 10-fold variation in clearance of CYP3A probe drugs (Floyd et al, 2003;Rogers et al, 2003), although 90-fold variability in CYP3A4 protein expression has been reported in liver (Lamba et al, 2002a). Some of the variation occurs because in the general population, CYP3A activity can be influenced by concurrent administration of CYP3A inhibitors and inducers.…”
mentioning
confidence: 99%